Demolition site at Pemberton Square, ca. 1896 - Black (Tufts Archival Research Center, 2005)
Demolition site located at Pemberton Square. Houses are included in the photograph. 4 5/8 x 7 1/8, 5 1/4 x 8 1/2 overall Cabinet photographs